Analysis of the impact of agricultural policy on potato production in Syria using the Agricultural Policy Analysis Matrix (PAM) - نزيه سفاف محمد جعفر; حيان سليمان (Latakia University Journal -Biological Sciences Series, 2025)
The research aimed to study and analyze the agricultural policies followed regarding the potato crop in the year 2023 using the Agricultural Policy Analysis Matrix (PAM), and to study the impact of the policy followed on the production of the crop using indicators of efficiency and economic competitiveness. The research adopted descriptive and quantitative analytical approaches, using mathematical and statistical methods and using some economic analysis methods to express economic variables such as revenues and costs and estimating the agricultural policy analysis matrix for the potato crop, using economic indicators of the impact of agricultural policy through three aspects: measuring nominal and effective protection coefficients, measuring Comparative advantage through the local resource cost factor, measuring the financial profitability of the farmer and the economic state of the country. The results of the research showed that the net transfer (L) of agricultural policies affecting the crop is negative, and this means that the policies applied do not work for the benefit of the producer. The nominal protection coefficient for outputs (NPCO) reached 0.55 (less than one), and this means that farmers get less profit if Merchandise trade is free, and the nominal protection coefficient for inputs (NPCi) is 0.47, and the effective protection coefficient (EPC) is 0.56 (less than one). This means that the overall impact of the policy outcomes indicates negative effects (taxes). The results of the analysis showed that the potato crop enjoys a comparative advantage, as the local resource cost (DRC) coefficient reached 0.05 (less than one). This means that the cost of the local worker is less than the social profit. The results also indicated that producing the crop is profitable for the farmer and the money invested in growing the crop is less than the value added achieved, as the private cost ratio (PCR) coefficient reached 0.08 (less than one), and the value of the support for agricultural producers (SRP) coefficient indicated that the applied agricultural policy does not support Product where the index value is -0.40 (less than zero).